Early onset pre-eclampsia: recognition of underlying renal disease. Issue 6564 (10th January 1987) - Ihle, B U; Long, P; Oats, J
Abstract : A follow up study of 84 patients with early onset pre-eclampsia (before 37 weeks' gestation) showed a high prevalence of underlying renal disease. Renal abnormalities were found in 33 of the 49 primiparas (67%) and in 22 of the 35 multiparas (63%). Two thirds of the multiparas with pre-eclampsia before 37 weeks with a diagnosis of either essential hypertension or renal disease had recurrent pre-eclampsia. Maternal morbidity and fetal mortality were greater in the group with early onset pre-eclampsia than in a group with late onset disease. Idiopathic pre-eclampsia occurred in 10% of primiparas in the early onset group, whereas it was the main condition in over three quarters of primiparas in the late onset group. A presumptive diagnosis of idiopathic pre-eclampsia is likely to be correct only in primiparas who develop the disease after 37 weeks of pregnancy; in all other cases careful search will almost certainly detect an underlying abnormality, predominantly renal.